BREAKING BARRIER:WORK FAMILY CONFLICT, GLASS CEILING AND FEMALE LECTURER PERFORMANCE - Astra Terenggana, Candra; Leovani, Ega (Jurnal Keuangan dan Bisnis, 2025)
PurposeThis study aims to investigate the influence of work-family conflict and the glass ceiling on the performance of female lecturers in higher education institutions, with job satisfaction examined as a mediating variable. Design/methodology/approachA quantitative research approach was employed, utilizing a survey method to collect data from 98 female lecturers affiliated with the APTIK network. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the hypothesized relationships among variables. FindingsThe results demonstrate that both work-family conflict and the glass ceiling have significant negative effects on job satisfaction. Furthermore, job satisfaction is proven to mediate the relationship between these factors and female lecturer performance. These findings highlight the critical role of psychological well-being in enhancing academic performance among female lecturers. Practical implicationsThe study provides actionable insights for human resource management in higher education institutions to design effective policies and interventions aimed at reducing work-family conflict and breaking the glass ceiling. Enhancing job satisfaction can be a strategic approach to improving lecturer performance. Originality/valueThis research offers empirical evidence on the mediating role of job satisfaction in the relationship between work-family conflict, the glass ceiling, and lecturer performance. The study contributes to the limited body of knowledge focusing on female academic staff within the APTIK network, offering valuable guidance for institutional development and gender equity initiatives. KeywordsWork-family conflict, Glass ceiling, Lecturer performance, Job satisfaction, Female lecturers, Higher education